A crítica nietzschiana ao sujeito e o estatuto do corpo - Rodrigues, Nelson Lopes (2023)
The present research proposes to understand Nietzsche's critique of the concept of subject and the importance of the statute of the body as the leading conductive thread of his critique in the historical context of the metaphysical tradition. According to Nietzsche, philosophy has conventionalized the idea of a subject with "atomistic" characteristics, as if it were an essentialist category. In this dissertation, we will investigate the concepts of "I", subject, consciousness, and subjectivity in the light of Nietzsche's notion of physio-psychology as established in the late phase of his philosophy. The body is the conductive thread that leads to the philosopher's critique of the idea of a metaphysical subject; the body understood as a structure of many souls, is the same as many struggles between wills of power, and hence, for Nietzsche, there is nothing like “one” subject, nor there is something as a sovereign "I". In Nietzsche's philosophy, this biological organization, that is the body, is understood as a hierarchical form of instincts that fight between themselves for a plus of strength; a conception whose foundation is his doctrine of the will to power. The relevance of this research consists in the attempt to demonstrate that Nietzsche is a radical critic of the notion of subject, based on the status of the body. The research concludes itself with the idea that the body is, for the philosopher, the consequence of a hierarchical organization between wills, as well as with the idea that our perception of the “I” as a unity is due to an interpretation of exhausted bodies.